2015
DOI: 10.1007/s12274-014-0650-5
|View full text |Cite
|
Sign up to set email alerts
|

Optical response and SERS properties of individual large scale supracrystals made of small silver nanocrystals

Abstract: There is a considerable interest for producing and understanding the optical and spectroscopic properties of ordered nanoparticles assemblies. Herein, we describe and interpret the optical absorbance and Raman properties of silver 5.9  0.3 nm diameter nanocrystals coated with dodecanethiol organized in highly ordered 3D superlattices of different heights. Each superlattice could be studied individually. A model based on Maxwell-Garnett formulation reproduces qualitatively the height and wavelength dependence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 73 publications
0
38
0
Order By: Relevance
“…We demonstrated very recently that silver NPs (5.9±0.3) nm in diameter, self‐organized by evaporation of a colloidal solution on a solid substrate, lead to important EFs ( around 10 4 ) even for surrounding alkyl ligands characterized by a low Raman cross‐section. Furthermore, the ligands were shown to not prevent the detection of other SERS‐active molecules, such as thiophenol …”
Section: Introductionmentioning
confidence: 49%
See 3 more Smart Citations
“…We demonstrated very recently that silver NPs (5.9±0.3) nm in diameter, self‐organized by evaporation of a colloidal solution on a solid substrate, lead to important EFs ( around 10 4 ) even for surrounding alkyl ligands characterized by a low Raman cross‐section. Furthermore, the ligands were shown to not prevent the detection of other SERS‐active molecules, such as thiophenol …”
Section: Introductionmentioning
confidence: 49%
“…Note that the optical properties of the samples depend on the dielectric properties of both the NP SLs and the substrate. The substrate effect was thus taken into account by using the Tomlin Model . Furthermore, this model allowed us to take into account the interference phenomena.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The optical properties of similar supercrystals of AgNCs have been recently examined, and it has been shown that a collective behavior is reflected in plasmonic properties due to long‐range dipolar interaction between neighboring NCs. The localized surface plasmon resonance (SPR), localized at 420 or 410 nm for isolated spherical nm‐sized AgNCs in colloidal suspensions or embedded in silica, is splitted in transverse and longitudinal SPR by their mutual coupling.…”
Section: Resultsmentioning
confidence: 99%